Orthonasal olfactory influences on consumer food behaviour - Zhang, T; Spence, C (Elsevier, 2023)
It is often suggested in the popular press that food chains deliberately introduce enticing product aromas into (and in the immediate vicinity of) their premises in order to attract customers. However, despite the widespread use of odours in the field of sensory marketing, laboratory research suggests that their effectiveness in modulating people's food behaviours depends on a range of contextual factors. Given the evidence that has been published to date, only under a subset of conditions is there likely a measurable effect of the presence of ambient odours on people's food attitudes and choices. This narrative historical review summarizes the various ways in which food odours appear to bias people's food preferences (appetite) and food choices (food consumption and purchase). Emphasis is placed on those experimental studies that have been designed to investigate how the characteristics of the olfactory stimuli (e.g., the congruency between the olfactory cues and the foods, intensity and duration of exposure to odours, and taste properties of odours) modulate the effects of olfactory cues on food behaviour. The review also explores the moderating roles of individual differences, such as dietary restraint, Body Mass Index (BMI), genetic and cultural differences in odour sensitivity and perception. Ultimately, following a review of empirical studies on food-related olfaction, current approaches in scent marketing are discussed and a research agenda is proposed to help encourage further studies on the effective application of scents in promoting healthy foods.